TINJAUAN YURIDIS TINDAKAN GREENWASHING OLEH LEMBAGA PERBANKAN DI INDONESIA BERDASARKAN PRINSIP ESG DAN HUKUM NASIONAL - Jasmine, Alifia (Jurnal Darma Agung, 2024)
The existence of various problems in the world has prompted changes in orientation in various business sectors, including banking. Currently, the banking sector is trying to echo the Sustainable Finance Concept and apply Environmental, Social, Government (ESG) Principles in every product and service. Unfortunately, in practice in the field, it was found that there were irregularities in its implementation carried out by banking institutions in the form of greenwashing practices. By using normative juridical methods, this research will use statutory approach and conceptual approach in explaining the phenomenon of greenwashing carried out by banking institutions. This research will use various legal materials, both primary, tertiary and secondary, to answer greenwashing practices carried out by banking institutions as well as law enforcement efforts that can be carried out by the government to eradicate greenwashing practices. Eradicating greenwashing practices is very important so that implementing the Sustainable Finance Concept and ESG Principles can have a real impact on the environment and solve problems that occur in the world.